Molecular architecture and microporous structure of low mature lacustrine kerogen: A multi-parameter modeling of the Triassic Yanchang Formation, Ordos Basin - Yinhai Song; Meijun Li; Xiaoqiang Liu; Xia Luo; Qingyong Luo; Qingbin Xie; Haochen Chen; Zhihao Wang (Fuel, 2027)

Study on three-dimensional multiphysics-coupled load-following operation of small lead-cooled fast reactors for grid peak shaving - Haochen Huang; Daogang Lu; Yu Liu; Yuchao Wang; Hao Ding; Danting Sui (Annals of Nuclear Energy, 2026)

Three-dimensional printed zerovalent iron enables selective and sustained reductive dehalogenation of florfenicol via structure-induced corrosion resistance and electron transfer regulation - Dan Li; Lu Liu; Haochen Li; Tao Ye; Junhong Wu; Jiaying Li; Si Zhai; Mengli Li; Huigai Wei; Lei Li; Jianhui Xu; Peng Liu; et al. (Environmental Research, 2026)

End-of-life allocation shapes carbon accounting and technology appraisal in life cycle assessment of electric vehicles across multi-generation cascades - Ziang Liu; Guangming Li; Haochen Zhu; Haoyuan Deng; Wenzhi He (Waste Management, 2026)

Eco-friendly fluidized solidified loess incorporating multi-source industrial solid wastes: A systematic study from rheological features, mechanical performance, and stabilization mechanisms - Baofeng Lei; Jucong Sun; Henghui Fan; Yongxiang Cao; Changhao Liu; Haochen Zhang; Shuai Pang; Jiaze Li; Huihui Yu; Minqiang Meng (Process Safety and Environmental Protection, 2026)

Hydrogen radical is also a critical reductive defluorination species in the Far-UVC-activated sulfite process - Xiangyang Hou; Shu Xu; Qiuling Lu; Kai Wang; Haonan Lu; Haochen Zhang; Yuying Li; Minchao Liu; Jin Jiang; Shuo Li; Jun Ma; Tiangang Luan; et al. (Journal of Hazardous Materials, 2026)

Solar light irradiation activated dichloramine for efficient abatement of micropollutants - Peng Su; Wenjun Zhang; Haochen Zhang; Haonan Lu; Qiuling Lu; Kai Wang; Yuying Li; Xiaolong Xu; Changyu Liu; Jun Ma; Tao Yang (Water Research, 2026)

Research on expansion of hydraulic fractures based on reservoir architecture: implications for well spacing in the northern Ordos Basin tight gas reservoir - Lei Bao; Qi Chen; Yuming Liu; Haochen Liu; Minghao Zhao; Xinqiang Liu; Jiagen Hou (Physics and Chemistry of the Earth, Parts A/B/C, 2026)

Integrated system dynamics and life cycle assessment modeling for carbon mitigation pathways in China's industrial mariculture - Fengfan Han; Yang Bai; Zilun Yi; Fei Jia; Haochen Hou; Ying Liu (Ecological Modelling, 2026)

Assessing the coupling coordination degree of energy-economy-environment and influencing factors in China's industrial mariculture: from a life cycle perspective - Fengfan Han; Yang Bai; Fei Jia; Haochen Hou; Zhen Ma; Ying Liu (Aquacultural Engineering, 2026)

Optimizing regional nitrogen management for intensive rice systems: A machine learning-based framework for reconciling agronomic nitrogen demands with environmental constraints - Zenghui Liang; Zhongwei Li; Haochen Li; Qiang Cao; Yongchao Tian; Yan Zhu; Weixing Cao; Zhaopeng Fu; Xiaojun Liu (Agricultural Systems, 2026)

Insight into poplar fractionation enhancement via an eco-manufacturing process using sulfonated magnetic polystyrene solid acid and biphasic solvent - Haochen Du; Cuiyi Liang; Shijun Liu; Xuesong Tan; Yang Chen; Shiyou Xing; Yu Zhang; Wei Liu; Wen Wang; Xin Shi; Zhongming Wang; Wei Qi (Chemical Engineering Journal, 2026)

Patterns and causes of ammonia nitrogen enrichment in groundwater of a typical agricultural irrigation area in the northern Henan Plain, China - Haoyang Li; Liang Zhang; Mingming Luo; Xiaoyang Liu; Gaoxin Xiao; Ruihua Shang; Shuna Sun; Haochen Gu; Chengyi Zu (Environmental Geochemistry and Health, 2026)

High-temperature corrosion mechanism of ferritic stainless steel in steam-hydrogen atmosphere for solid oxide electrolysis cell based on reactive force field method - Enhua Wang; Yajing Zhang; Jingwen Mao; Haochen Dang; Minggao Ouyang; Haoran Hu; Hewu Wang; Yadi Liu; Youpeng Chen; Languang Lu; Dongsheng Ren (Fuel, 2026)

From behavior to taste: Developmental trajectories of anxiety-like phenotypes unveil a neuroendocrine link to flesh quality in economic crustaceans - Hengtong Liu; Sisi Sheng; Yiming Li; Wanting Huang; Wenbin Liu; Haochen Wang; Cheng Chi; Dingdong Zhang (Food Bioscience, 2026)

CitrusNet: A vision transformer-CNN approach for citrus detection from multi-source imagery with multi-scale feature integration - Haochen Wang; Juan Shi; Hamed Karimian; Fei Wang; Faizan Javed; Bo Liu; Shengnan Shi; Ziwei Li; Yang Tao (Computers and Electronics in Agriculture, 2026)

Bead-chain like Zr-MOF@polypyrrole nanotube conductive composites for efficient capacitive defluorination - Feng Xiao; Hao Zhang; Huabin Han; Chang Guo; Haochen Zhu; Yuchen Liu; Yanhui Wu (Journal of Environmental Chemical Engineering, 2026)

Mobile MAX-DOAS measurements and source analysis of NO2, HCHO, and HONO during the Chengdu 2023 FISU world university games - Qijin Zhang; Chengzhi Xing; Miao Feng; Yinshuo Ding; Zhongmou Sun; Yikai Li; Haochen Peng; Wei Tan; Zhiguo Zhang; Tianjun Du; Cheng Liu (Journal of Environmental Sciences, 2026)

Is south-north relay aquaculture sustainable? Life cycle assessment of the Manila clam (Ruditapes philippinarum) supply chain in China - Fei Jia; Fengfan Han; Jie Song; Anqi Ren; Yang Bai; Haochen Hou; Zhongming Huo; Ying Liu (Aquaculture International, 2026)

Close-packed metal organic frameworks enabled high-energy solid-state lithium metal batteries - Yining Zhang; Hongsheng Shi; Yuyao Zhang; Xin Chen; Shuanghong Wang; Jinjiang Liang; Qiong Yuan; Tianyi Gao; Ran Wei; Haochen Zhang; Tao Li; Tianquan Lin; et al. (Chemical Engineering Journal, 2026)

Effectiveness of MTMD for jacket offshore platform under wave and earthquake excitations - Shutong Liu; Xunhe Yin; Haochen Li; Jingchao Yang; Peizhen Li; Peng Li (Soil Dynamics and Earthquake Engineering, 2025)

Quantitative effects of potassium application on potato tuber yield, quality, and potassium uptake in China: A meta-analysis - Fan Zhang; Xiukang Wang; Hao He; Haochen Wang; Bolun Zhang; Shiju Liu; Ruixue Chen; Yaru Zhang; Yandong Wang; Hao Ren; Yu Wang; Juan Han (Field Crops Research, 2025)

Piezo1: the Potential Novel Target for Radiation-induced Liver Fibrosis by Regulating FAP + fibroblasts - Wentong Liu; Haochen Zou; Jiaying Wei; Lihua Dong; Wei Hou (Molecular and Cellular Biochemistry, 2025)

Seismic response and failure evolution of an irregular slope containing bedding planes and high-position surficial soil layer - Qianqian Feng; Yunsheng Wang; Jianxian He; Xiaolong Hu; Haochen Wu; Dongyu Hu; Shicheng Liu; Tao Tang (Landslides, 2025)

Efficient permanganate activation under UV 222 nm irradiation for enhanced pollutant abatement - Haochen Zhang; Peng Su; Maoju Jiang; Chenlong Liu; Qixiao Lv; Wenqi Li; Xiangyang Hou; Junhui Zhou; Shuo Li; Bin Zhang; Bei Zhang; Jun Ma; et al. (Water Research, 2025)

High-touch surfaces with moderate contamination levels as key nodes in microbial dissemination - Pengcheng Zhao; Peihua Wang; Tzehau Lam; Nan Zhang; Huanhuan Wang; Haochen Zhang; Jiquan Liu; Yuguo Li (Journal of Hazardous Materials, 2025)

Spatiotemporal variability of soil moisture and its influencing factors in a forested catchment with complex terrain - Haochen Liu; Shangqiang Hui; Yuting Zhao; Yanjia Jiang; Yongliang Qi; Elizabeth W. Boyer; Carlos R. Mello; Li Guo; Hongxia Li (CATENA, 2025)

Icing monitoring technology and application of 10 kV overhead distribution lines based on axial tension measurement - Lin Yang; Lulu Mei; Haochen He; Quan Liu; Yanpeng Hao; Licheng Li; Xinhao Lin (Cold Regions Science and Technology, 2025)

Mechanism of reducing antibiotic resistance genes by nano-selenium during composting: insight into host microorganisms and a two-component system - Xi Chen; Muqing Zhan; Haochen Shao; Shuangshuang Ma; Li Liu; Zuyong Chen; Chen Fang (Journal of Environmental Management, 2025)

Intergeneric protoplast fusion for probiotic strain improvement: Molecular mechanisms and metabolic analysis - Haiting Duan; Xin Su; Qiqi Fan; Haochen Zhang; Bilige Menghe; Wenjun Liu (Food Bioscience, 2025)

Delineating and refining the equity of revealed accessibility of express service amenities: A case study of Guangzhou - Yankai Wang; Quanyu Liu; Tao Mei; Haochen Shi; Miaoxi Zhao; Binbin Sun (Applied Geography, 2025)

Light-enhanced ion transport and fouling resistance properties of metal/semiconductor heterojunction nanochannel membranes for osmotic energy recovery in real-world conditions - Haochen Lu; Jin Wang; Derong Zhang; Tongxin Liao; Shangzhen Li; Lei Lei; Zhiyan Liu; Bingjie Du; Xudong Wang; Lei Wang (Water Research, 2025)

Thermokinetic analysis of surface-active groups in coal using ultrasonic extraction method - Yaqing Li; Xinxin Sun; Yutao Zhang; Jun Deng; Kexin Liu; Yuanbo Zhang; Qiang Guo; Haochen Li (Fuel, 2025)

The outer-inner loop mechanism of alkali carbonate-modified BaFe2O4 during the biomass char chemical looping partial oxidation and hydrogen generation (CLPH) process - Haochen Sun; Hengyang Miao; Zhiqing Wang; Zheyu Liu; Chao He; Yitian Fang (Chemical Engineering Journal, 2025)

Facile formation of van der Waals metal contact with III-nitride semiconductors - Xiyu Sun; Danhao Wang; Xiaojing Wu; Jiahao Zhang; Yangjian Lin; Dongyang Luo; Fang Li; Haochen Zhang; Wei Chen; Xin Liu; Yang Kang; Huabin Yu; et al. (Science Bulletin, 2024)

Shaking table test and numerical simulation of jacket offshore platform considering soil-water-structure interaction - Shutong Liu; Haochen Li; Jin Zhang; Shutong Yang; Tianyu Zhang (Ocean Engineering, 2024)

A study of wave forces on a vertical truncated cylinder with different submergence depths - Yuping Fan; Jinxuan Li; Shuxue Liu; Haochen Zhang (Ocean Engineering, 2024)

Enhanced peracetic acid activation under Far-UVC Radiation: Micropollutant degradation and radical assessment - Tao Yang; Maoju Jiang; Peng Su; Qixiao Lv; Wenqi Li; Chenlong Liu; Bin Zhang; Haochen Zhang; Linlin Zang; Minchao Liu; Jun Ma (Chemical Engineering Journal, 2024)

Differential impacts of microplastics on carbon and nitrogen cycling in plant-soil systems: A meta-analysis - Yige Liu; Siyi Chen; Pengyu Zhou; Haochen Li; Quan Wan; Ying Lu; Bo Li (Science of The Total Environment, 2024)

Experimental and numerical analysis of wave forces on a vertical truncated cylinder with different depths of submergence under focused waves - Yuping Fan; Jinxuan Li; Shuxue Liu; Haochen Zhang (Ocean Engineering, 2024)

Dietary flavonoids: Role in preventing neurodegenerative diseases caused by brain aging by modulating the gut microbiota - Siyu Liu; Haochen Dai; Rui Wang; Xin Zhang (Food Bioscience, 2024)

From trajectories to network: Delineating the spatial pattern of recreational walking in Guangzhou - Haochen Shi; Linlin Yao; Qiqi Liu; Yankai Wang; Zongcai Wei; Miaoxi Zhao; Ding Ma (Applied Geography, 2024)

A multi-objective optimization approach for green supply chain network design for the sea cucumber (Apostichopus japonicus) industry - Anqi Ren; Lixingbo Yu; Xintao Zhao; Fei Jia; Fengfan Han; Haochen Hou; Ying Liu (Science of The Total Environment, 2024)

Dietary flavonoids modulate the gut microbiota: A new perspective on improving autism spectrum disorder through the gut-brain axis - Haochen Dai; Yuhan Jiang; Shuxun Liu; Dandan Li; Xin Zhang (Food Research International, 2024)

Studies on regional ozone formation sensitivities and transport with higher spatiotemporal resolutions in a stereoscopic dimension: GEMS and vertical observations - Haochen Peng; Chengzhi Xing; Yikai Li; Chengxin Zhang; Jinan Lin; Jingkai Xue; Xiaohan Wang; Yuhang Song; Xinhan Niu; Cheng Liu (Atmospheric Research, 2024)

The pyrolysis of 4,4,8,10-tetramethyl decalin and the influence of molecular structures on oil thermal cracking: A ReaxFF molecular dynamics simulation and DFT study - Haochen Chen; Meijun Li; Xiaoqiang Liu; Qiuya Han; Wenke Li; Siyuan Zhang (Fuel, 2024)

A numerical study on autoignition of finite thick polymethyl methacrylate (PMMA) subjected to thermal radiation and forced airflow - Haochen Lian; Yu Fang; Bo Liu; Junhui Gong (Fuel, 2024)

Engineering mesoporous nascent MnO2 colloids for efficient elimination of emerging organic contaminants - Zhuoyue Liu; Dong Cheng; Haochen Yin; Jianghao Zhao; Jiale Zhang; Rongzhi Chen; Shengjiong Yang; Jing Wei; Gen Wang (Journal of Water Process Engineering, 2024)

One-step strategy for efficient Cr(VI) removal via phytate modified zero-valent iron: Accelerated electron transfer and enhanced coordination effect - Rui Gan; Yuxuan Ye; Ziyi Zhan; Qiuyue Zhang; Yuwei Deng; Yingjie Liu; Haochen Li; Jun Wan; Xuanyuan Pei; Qiang Li; Fei Pan (Journal of Hazardous Materials, 2024)

Highly efficient adsorption of ciprofloxacin from aqueous solutions by waste cation exchange resin-based activated carbons: Performance, mechanism, and theoretical calculation - Qiang Li; Haochen Li; Xiaofei Zong; Haochao Sun; Yunhao Liu; Ziyi Zhan; Shou Mei; Yanjie Qi; Yangbo Huang; Yuxuan Ye; Fei Pan (Science of The Total Environment, 2024)

Enhancing column bioleaching of chalcocite by isolated iron metabolism partners Leptospirillum ferriphilum/Acidiphilium sp. coupling with systematically utilizing cellulosic waste - Xingyu Huo; Jianna Liu; Xianjing Hong; Haochen Bai; Zongling Chen; Jinming Che; Hailin Yang; Yanjun Tong; Shoushuai Feng (Bioresource Technology, 2024)

Spatial patterns of zooplankton abundance, biovolume, and size structure in response to environmental variables: a case study in the Yellow Sea and East China Sea - Song Sun; Haochen Xian; Xiaoxia Sun; Mingliang Zhu; Mengtan Liu (Journal of Oceanology and Limnology, 2024)

Long-term observations of NO2 using GEMS in China: Validations and regional transport - Yikai Li; Chengzhi Xing; Haochen Peng; Yuhang Song; Chengxin Zhang; Jingkai Xue; Xinhan Niu; Cheng Liu (Science of The Total Environment, 2023)

Recognizing iso-olefins as paramount intermediates for optimum isoparaffins production via CO hydrogenation - Haochen Qi; Cederick Cyril Amoo; Wuqiang Si; Jian Lou; Xuangan Liu; Chunyang Zeng; Qingjie Ge; Jian Sun; Chuang Xing; Xinhua Gao (Fuel, 2023)

The fate of microplastic pollution in the Changjiang River estuary: A review - Yifei Li; Qingbing Lu; Jian Yang; Yi Xing; Wei Ling; Kai Liu; Qizhen Yang; Hongjie Ma; Zengxin Pei; Tianqi Wu; Haochen Guo; Ziyuan Gao; et al. (Journal of Cleaner Production, 2023)

The impact of the streetscape built environment on recreation satisfaction: A case study of Guangzhou - Haochen Shi; Lijun Yu; Yaogeng Xu; Yuqi Liu; Miaoxi Zhao (Journal of Transport Geography, 2023)

An epoxide-based covalent sensor to detect cardiac proteome aggregation in a cardio-oncology model - Hao Jin; Di Shen; Biao Jing; Zhenduo Zhang; Zhiming Wang; Rui Sun; Huaiyue Zhang; Jialu Sun; Haochen Lyu; Yu Liu; Lili Wang (Analytica Chimica Acta, 2023)

Enhanced hydroxyl radical generation for micropollutant degradation in the In2O3/Vis-LED process through the addition of periodate - Tao Yang; Linqian An; Ge Zeng; Jiamin Mai; Yuying Li; Jinchuan Lian; Haochen Zhang; Juan Li; Xiaoxiang Cheng; Jianbo Jia; Minchao Liu; Jun Ma (Water Research, 2023)

Numerical investigation of suppressing thermal runaway propagation in a lithium-ion battery pack using thermal insulators - Junhui Gong; Bo Liu; Haochen Lian; Jingyi Liu; Hui Fu; Yuxuan Miao; Jialong Liu (Process Safety and Environmental Protection, 2023)

One-step and real-time detection of Hg2+ in brown rice flour using a biosensor integrated with AC electrothermal enrichment - Haochen Qi; Lei Xiao; Jayne Wu; Li Lv; Xinyu Hu; Youyi Zhuang; Xiaoru Liu; Wenci Zhao; Fangshuo You; Jian Zhang; Lei Zheng (Food Chemistry, 2023)

Remediation of sulfonamides-contaminated groundwater through in-situ activation of peroxymonosulfate by supported hierarchical CuO/MgO nanosheets - Zhuoyue Liu; Lei Ge; Ke Wang; Haochen Yin; Danyang Li; Shengjiong Yang; Gen Wang; Delu Miao (Journal of Water Process Engineering, 2023)

Adversarial interspecies relationships facilitate population suppression by gene drive in spatially explicit models - Yiran Liu; WeiJian Teo; Haochen Yang; Jackson Champer (Ecology Letters, 2023)
Suppression gene drives bias their inheritance to spread through a population, potentially eliminating it when they reach high frequency. CRISPR homing suppression drives have already seen success in the laboratory, but several models predict that success may be elusive in population with realistic spatial structure due to extinction‐recolonization cycles. Here, we extend our continuous space framework to include two competing species or predator–prey pairs. We find that in both general and mosquito‐specific models, competing species or predators can facilitate drive‐based suppression, albeit at the cost of an increased rate of drive loss outcomes. These results are robust in mosquito models with seasonal fluctuations. Our study illustrates the difficulty of predicting outcomes in complex ecosystems. However, our results are promising for the prospects of less powerful suppression gene drives to successfully eliminate target mosquito and other pest populations.

Occurrence, source apportionment and ecological risk assessment of thirty antibiotics in farmland system - Jinghua Ren; Haochen Shi; Jianchao Liu; Chaoya Zheng; Guanghua Lu; Shefeng Hao; Yang Jin; Chao He (Journal of Environmental Management, 2023)

Comparative genomics revealed that Vibrio furnissii and Vibrio fluvialis have mutations in genes related to T6SS1 and T6SS2 - Jiakai Sun; Haochen Su; Wenhui Zhang; Xuesong Luo; Ruichao Li; Ming Liu (Archives of Microbiology, 2023)

CFSA-AGD: An accurate crosstalk fluorescence spectroscopic decomposition method for identifying and quantifying FDOMs in aquatic environments - Yuchao Fu; Wanxiang Li; Tianyuan Liu; Zhen Zhang; Haochen Li; Jingran Xu; Meizhen Huang (Science of The Total Environment, 2023)

Metallurgical performance and structural characteristics of cokes of hypercoal prepared from the mixture of low-rank coal and biomass residue - Jun Zhao; Hong Liu; Haochen Zhang; Xiaolin Song; Haibin Zuo; Guangwei Wang; Zhigao Xu; Ming Wu; Zhenyue Zhang; Ru'an Chi (Fuel, 2023)

Green credit policy and the liquidity risks of heavily polluting enterprises - Tuo Wang; Xiaoxing Liu; Haochen Guo (Environmental Science and Pollution Research, 2022)

Autophagy regulation of ATG13 and ATG27 on biofilm formation and antifungal resistance in Candida albicans - Siqi Liu; Liuliu Jiang; Haochen Miao; Ying Lv; Qinqin Zhang; Ming Ma; Wei Duan; Yun Huang; Xin Wei (Biofouling, 2022)

Meshless Surface Wind Speed Field Reconstruction Based on Machine Learning - Nian Liu; Zhongwei Yan; Xuan Tong; Jiang Jiang; Haochen Li; Jiangjiang Xia; Xiao Lou; Rui Ren; Yi Fang (Advances in Atmospheric Sciences, 2022)

Numerical investigations on load transfer of mooring line considering chain–seabed dynamic interaction - Shengjie Rui; Zhen Guo; Lizhong Wang; Haochen Liu; Wenjie Zhou (Marine Georesources & Geotechnology, 2021)

Omega-3 fatty acid protects cardiomyocytes against hypoxia-induced injury through targeting MiR-210-3p/CASP8AP2 axis - Xueju Yu; Fengyao Liu; Yuting Liu; Bingqing Bai; Han Yin; Haochen Wang; Yingqing Feng; Huan Ma; Qingshan Geng (Molecular and Cellular Biochemistry, 2021)

TCDD induced lipid accumulation by impairment of autophagic flux in THP-1 macrophages - Jing Lu; Meitong Liu; Yong Fan; Haochen Zheng; Shuang Guan (Environmental Science and Pollution Research, 2021)

Reclamation of desert land to continuous cotton cropping affects soil properties and microbial communities in the desert-oasis ecotone of Xinjiang, China - Jinbiao Li; Guangming Liu; Jin-Hyeob Kwak; Scott X. Chang; Haochen Gao; Qicong Wu; Jingsong Yang; Jinlin Chen (Journal of Soils and Sediments, 2020)

Comparison of different sequential extraction procedures for mercury fractionation in polluted soils - Haochen Dong; Liu Feng; Yu Qin; Muxinjian Luo (Environmental Science and Pollution Research, 2019)